Effect of radio frequency power on a-CNx film properties and its performance as humidity sensors - Rozidawati Awang,; Noorain Purhanudin,; Nur Sakinah Salman, (Penerbit Universiti Kebangsaan Malaysia, 2018)
A series of amorphous carbon nitride (a-CNx) thin films were deposited on silicon (111) substrates using a home-built radio frequency plasma enhanced chemical vapor deposition (RF-PECVD) system. The a-CNx thin films were deposited from a mixture of a fixed flow-rate of ethane (C2H6, 20 sccm) and nitrogen (N2, 47 sccm) gases with varying RF power. A higher ratio of C to H (C to H ratio is 1:3) atoms in C2H6 as compared to the ratio in methane (CH4) gas (C to H ratio is 1:4) is expected to produce an interesting effect to the film properties as humidity sensor. The characterization techniques used to determine the morphology and chemical bonding of the thin films are field emission scanning electron microscopy (FESEM) and Fourier transform infrared spectroscopy (FTIR), respectively. The variation of morphology and the existence of nitrile band in these samples are correlated with the electrical properties of a-CNx thin films. Using humidity sensing system, the sensing performance of the samples was examined. It was found that the response of sensors towards the percentage of relative humidity (% RH) change is good resistive responses and good repeatability. The sensitivity of the prepared a-CNx thin films is significantly higher (up to 79%) as compared to previous studies using CH4 or acetylene as precursor gas. Based on these results, the properties and the sensitivity of the a-CNx thin films towards humidity can be tailored by using an appropriate precursor gases and deposition parameters.